Employee Retention Management: long-term retention of employees – a comparison of generations - Katrin Winkler; Christina Saur (Journal of Applied Leadership and Management, 2019)
Research questions: Which factors influence the long-term retention of employees? What differences can be found in the characteristics of different generations and to what extent is generation specific Employee Retention Management (ERM) necessary for long-term retention? Which measures and possible actions can be derived? Methods: Based on a theoretical approach and an overview of relevant models and literature, hands-on tools, which can strengthen the retention of employees to the company in a generation-specific way, are derived. Results: The paper results in the conclusion that retention of top performers in the company is indispensable in order to counteract current developments in the world of work. The generational diversity must be taken into account in the context of ERM. The differences between the generations Baby Boomer and Y are of particular interest and provide initial insights into the expectations of employees.
Keywords: 650